PENGARUH FRAKSI AIR DAUN KEDONDONG BANGKOK (Spondias dulcis) TERHADAP PENURUNAN KADAR GLUKOSA DARAH PADA MENCIT PUTIH JANTAN - Ramadhan Triyandi; Nopiyansyah Nopiyansyah; Robi Wira Pratama (JFL : Jurnal Farmasi Lampung, 2018)
Ambarella Bangkok fruit (Spondias dulcis) is fruits from Anacardiaceae family. Ambarella plant is known containing secondary metabolite compounds such as alkaloid, flavonoid, saponin and tannin. Flavonoid is a polyphenol compound which work as antioksdant. Ambarela Bangkok leaf containing rich antioksidant which can be use as prevention of cancer, heart disease, cholesterol, diabetes, and premature aging. The purpose of this research is to look effect from water fraction from Ambarela leaf (spondias dulcis) to decrease diabetes disease from white male mice. In this research ambarela leaf is extracted by maseration with 70% alcohol. After the extract obtained then fractionation prosen be held. From the fraction wich ocurred, then made three variant of dose those are 175.5 mg/kgW, 351 mg/kgW and 702 mg/kgW. From those three dose, the 702mg/ kgW dose has the best effect from another dose. Positive control used glibenclamide and negative control used aquadest. The result of this research shows that water fraction from Ambarela leaf can decrease diabetes desease from the white male mice. The the greater fraction concentration, the greater the concentration of the fraction then the decrease of blood glucose level in mice is getting better. The 702mg/kgW dose has an average value of decline 94.3 mg/Dl. The result of analisys shows that watter fraction of ambarella Bangkok leaf can decrease the blood glucose level in male white mice. Key word : Spondias dulcis, water fraction of Ambarela leaf , Blood glucose level